Anatomical success of tectonic keratoplasty in children at a tertiary care eye hospital - Hassan, Shadab; Noorani, Sorath; Zaheer, Naima; Jabeen, Sidra (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the anatomical outcome of tectonic grafts performed in children with perforated or melted corneas. Method: The prospective study was conducted at the Department of Paediatric Ophthalmology, Al-Shifa Trust Eye Hospital, Rawalpindi, Pakistan, from January to December 2017, and comprised children of either gender aged <16 years who received tectonic grafts owing to desmetocele or corneal perforation of >3mm. The causes of corneal perforation, size of perforation, post-operative graft outcome and globe integrity were noted. Periodic follow-ups were done till December 2019. Data was analysed using SPSS 22. Results: Of the 27 patients, 9(33.3%) were girls and 18(66.7%) were boys. The overall mean age was 47.7±43.5 months. The most common indication was corneal perforation 19(70.4%), followed by descemetocele 8(29.6%). The most frequent cause was infectious keratitis 13(48.2%), followed by trauma 8(29.6%) and vitamin A deficiency 5(18.5%). The mean size of perforation/descemetocele was 5.5±1.5mm. Post-operatively, graft failure occurred in 5(18.5%) eyes and required repeat grafts. Globe integrity was restored in all 27(100%) cases, and 24(88.8%) eyes maintained their size and intraocular pressure, while 3(11.1%) became phthisical. Post-operative visual acuity was better than 6/36 in 3(11.1%) eyes, between 6/36 and 6/60 in 10(37%) and counting finger in 14(51.8%). Conclusion: Tectonic graft was found to be a valuable therapeutic option in emergency globe-threatening corneal thinning and perforation and in maintaining the anatomical integrity of eyes. Key Words: Keratoplasty, Corneal perforation, Corneal grafting.